2020
DOI: 10.1155/2020/8865223
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-Eluting Balloon for the Treatment of Coronary Lesions in Complex ACS Patients: The SELFIE Registry

Abstract: Background. Sirolimus-coated balloons (SCBs) represent a novel therapeutic option for both in-stent restenosis (ISR) and de novo coronary lesions treatment, especially in small vessels. Our registry sought to evaluate the procedural and clinical outcomes of such devices in a complex acute coronary syndrome (ACS) clinical setting. Methods and Results. We treated 74 consecutive patients with percutaneous coronary intervention (PCI) with at least 1 SCB used for ISR and/or de novo coronary lesion in small vessels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, a retrospective study analyzed 222 patients with RVD ≥2.8 mm, and there was no TLR and MACE at an average of 10 months of follow-up ( 7 ). DCB-only strategy for native lesions of large coronary vessels has also shown promising results for specific indications, for example, patients with high bleeding risk or patients with complex acute coronary syndrome ( 15 , 16 ). Moreover, the incidence of TLF with DCB was comparable to TLF with newer-generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a retrospective study analyzed 222 patients with RVD ≥2.8 mm, and there was no TLR and MACE at an average of 10 months of follow-up ( 7 ). DCB-only strategy for native lesions of large coronary vessels has also shown promising results for specific indications, for example, patients with high bleeding risk or patients with complex acute coronary syndrome ( 15 , 16 ). Moreover, the incidence of TLF with DCB was comparable to TLF with newer-generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…A first indirect comparison between the MagicTouch SCB and PCB could not find significant differences in terms of safety and efficacy; at multivariable analysis, diabetes remained the only independent predictor of MACE [29]. The SCB used in our study is the first sirolimus-based balloon marketed in EU and has beenXXXrevioussly tested in small registries also in complex scenarios like ACS patients [30][31][32][33]. Two RCTs have been conceived to test the MagicTouch balloon [34,35].…”
Section: Discussionmentioning
confidence: 84%
“…There was one suspected subacute thrombosis (1.6%) but no significant bleeding. Patients treated for de novo lesions and ISR did not vary significantly in terms of MACE incidence in a subgroup analysis (HR: 0.239; CI 95%: 0.003–16.761) [ 54 ]. They concluded that it is safe and efficacious for the treatment; however, a larger population study is needed to confirm the findings.…”
Section: Drug-coated Balloonmentioning
confidence: 99%